PENGARUH NAUNGAN TERHADAP PERTUMBUHAN SEMAI MAKILA (Litsea angulata) - Edom Bayau (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2017)
Makila (Litsea angulata) is a type of commercial timber and is very attractive to many people because of good quality and can also be used as a medicine in curing rheumatic diseases should be assigned the paramount concern. cultivation / reproduce makila can be done in a fast way is through the nursery in the field. in nurseries should also pay attention to things that affect makila, one of which is related to the intensity of sunlight makila seedling growth. The research conducted at the location of the greenhouse Faculty of Agriculture, University of Pattimura which take place september until november 2014 with the aim to determine the seedling growth makila (Litsea angulata) to determine what percentage of shade is good for seedling growth makila (Litsea angulata). The experimental design used was completely randomized design (CRD) with 5 (five) treatments, the seedlings without using Shade, Shade 30 percent, 50 percent Shade, Shade 65 percent, and Shade 75 percent. The results showed that the seedling Makila (Litsea angulata) is a kind of tolerance with all shade or kind makila able to grow in places that are open and shaded place.